A Newly Emerging Thermal Area in Yellowstone - Vaughan, R. Greg; Hungerford, Jefferson D. G.; Keller, William (Frontiers in Earth Science, 2020)
Yellowstone National Park contains many dynamic thermal areas that are the surface expression of the deeper magmatic system. Recently, we discovered the emergence of a new thermal area, located near the northeast margin of the Sour Creek dome, between Tern Lake and a previously mapped thermal area. It was about 33,300 m2 in area and located in the backcountry. It was discovered in 2018 as a spatially anomalous area of warm pixels in a Landsat 8 nighttime thermal infrared image. A high-spatial-resolution airborne visible image from August 2017 revealed a large area of recently fallen trees, mostly devoid of vegetation, and with bright soil, similar to other nearby thermal areas. Field observations in August 2019 confirmed that this was a steam-heated acid-sulfate thermal area, with an arc-shaped zone of hydrothermally altered soil and heated ground, with surface temperatures of 60-80 °C, several steaming fumaroles, and boiling temperatures (93 °C) just beneath the surface. Fallen trees in contact with warm ground were being carbonized, yet there were some cooler areas with new trees growing. Archived satellite and airborne remote sensing data going back to 1994 revealed that this thermal area started emerging around 2000. It slowly increased in size and in heat output until around 2005. 2005 to 2012 was a period of more rapid growth. From 2012 to present the growth rate slowed and stabilized, showing relatively little change. The formation of this new thermal area was not clearly linked to distinct seismic or geodetic events, though the period of rapid growth did partly coincide with a period of rapid inflation, possibly suggesting a causative relationship. The identification of this emerging thermal area illustrates the importance of satellite thermal infrared imaging combined with high-spatial-resolution remote sensing data and field observations for mapping, measuring, and monitoring Yellowstone's thermal areas. It’s also an example of the dynamics we expect to observe within Yellowstone’s hydrothermal system. Changes in the size and distribution of such thermal areas constitute normal background hydrothermal activity at large caldera systems. This new thermal area does not appear to reflect any significant changes in the broader magmatic system.